UNPACKING TOURIST SATISFACTION IN HOTELS: A MULTI-DIMENSIONAL ANALYSIS BASED ON HOTEL TYPE, LOCATION, AND ONLINE REVIEW PLATFORMS - Wulandari, Zhafira Nisa; Akbar, Muhammad Alifh; Hananditya, Adinda Hanung; Zulfana, Marsa Farah; Avisa, Mianda Putri; Efendi, Dilla Rachmawati; Yi, Li Gu; Saihaloknya, Dwi Mela (Journal of Business Studies and Management Review, 2025)
This study explores the complex and multidimensional factors that influence tourist satisfaction in the hospitality industry, focusing specifically on the roles played by hotel type, geographic location, and online review platforms. Employing a systematic literature review (SLR) approach, the research analyzes 30 peer-reviewed journal articles published between 2018 and 2024, drawing insights from diverse disciplines including marketing, tourism studies, consumer behavior, data analytics, and digital technology. The findings highlight several key determinants of tourist satisfaction, such as service quality, perceived experiential value, levels of technological innovation, and the effectiveness of personalized marketing efforts. Additionally, variations in guest satisfaction are observed based on hotel classification (luxury, mid-range, or budget), physical location (urban centers, suburban areas, or popular tourist destinations), and the online platforms through which customer feedback is expressed (e.g., TripAdvisor, Google Reviews). This study offers a comprehensive synthesis of recent academic literature and provides practical recommendations for hotel managers to design more contextualized, data-informed strategies that elevate the guest experience and drive long-term loyalty.